Analisis Etika Kebahasaan Dalam Diplomasi - Nadziroh, Rimby; Feliciana Mokodompit, Anna Gabriella; Pramudya, Ryan Wahyu; Saputra, Riko Ferdian; Ahnaf, Muhammad; Nurhayati, Eni (LPPM STKIP PGRI Sidoarjo, 2024)
This paper is motivated by the author's interest in language ethics used in diplomacy practices. This paper will discuss how the use of language ethics can affect the relationship between diplomacy actors. The method used in this research is a descriptive study with a qualitative approach that will be supported by relevant literature obtained from various trusted sources such as books, journals, and the internet. The results obtained in this study are how language ethics in diplomacy can overcome various challenges faced such as differences in cultural backgrounds, languages, and dialects owned by each actor. The use of linguistic ethics is also considered capable of being an intermediary to build good diplomatic relations between the actors involved in it.